Molecular characterization and expressional quantification of lgp2, a modulatory co‐receptor of RLR‐signalling pathway in the Indian major carp Labeo rohita following pathogenic challenges and PAMP stimulations. Issue 6 (20th March 2020) - Mohanty, Arpita; Sadangi, Sushmita; Paichha, Mahismita; Samanta, Mrinal
Abstract: Lgp2 (laboratory of genetics and physiology 2) is a cytosolic viral sensor of the RLR (retinoic acid‐inducible gene 1 like receptor) family member without the caspase recruitment domain, having both inhibitory and stimulatory roles in RLR‐signalling pathway. In India, Labeo rohita (rohu) is one of the leading and economically favoured freshwater fish species. Several immunological sentry proteins have been reported in this fish species, but no information is available on the RLR members. This study was aimed at cloning and characterization of full‐length lgp2 ‐cDNA (complementary DNA) in rohu and investigation of its expressional modulations following various pathogen‐associated molecular pattern stimulations and bacterial infections. The full‐length lgp2 ‐cDNA sequence obtained through rapid amplification of cDNA ends‐PCR consisted of 2299 nucleotides with an open reading frame of 2034 bp encoding 677 amino acids. In rohu‐Lgp2, four conserved domains – a DEAD/DEAH box helicase domain, Pfam type‐III restriction enzyme domain, helicase superfamily c‐terminal domain and RIG‐I C‐terminal regulatory domain – have been detected. Within these domains, several important functional motifs, such as ATP‐binding site, ATPase motif, RNA unwinding motif and RNA‐binding sites, have also been identified. In healthy rohu, lgp2 gene was abundantly expressed in gill, liver, kidney, spleen and blood. In response to both in vitro and in vivo treatments using double‐stranded RNA (poly I:C), lgp2 gene expression was significantly ( P < 0.05) upregulated in all tested tissues and also in the LRG ( Labeo rohita gill) cells. lgp2 gene expression significantly ( P < 0.05) increased on stimulation of LRG cells using γ ‐d ‐glutamyl‐meso‐diaminopimelic acid and muramyl dipeptide. In vivo treatment using lipopolysaccharide and A eromonas hydrophila ‐derived RNA resulted in both up‐ and down‐regulation of lgp2 gene expression. Upon gram‐positive and gram‐negative bacterial infections, the expression of the lgp2 gene increased at different times in almost all the tested tissues. These integrated observations in rohu suggest that Lgp2 is an antiviral and antibacterial cytosolic receptor. Significance Statement: Lgp2, a cytosolic viral sensor of retinoic acid‐inducible gene 1 like receptor family member, has been cloned in Labeo rohita. The complete sequence of rohu lgp2 ‐complementary DNA consisted of 2299 nucleotides with an open reading frame of 2034 bp encoding 677 amino acids. It consisted of a DExDc, RES‐III, HELICc, Pfam RIG‐I_C‐RD, ATP‐binding site, ATPase motif, RNA unwinding motif and RNA‐binding site. Upon bacterial infection, double‐stranded RNA and various pathogen‐associated molecular pattern stimulations, lgp2 gene expression significantly increased, indicating its role as an antiviral and antibacterial cytosolic receptor.